Carbon Saving Potential in Several Types of Robusta Coffee-Based Agroforestry in Rowosari Village, Jember - Kharisma Wahyu Lestari; Nilasari Dewi (Jurnal Silvikultur Tropika, 2023)
The phenomenon of forest destruction can be found in various regions of the world through deforestation activities and has an impact on environmental sustainability. One of the impacts caused by climate change due to deforestation is at the same time threatening the activities of the agricultural sector, namely the sustainability of food production. Agroforestry is a sustainable agricultural system by cultivating tree components with agricultural plant species. The role of trees in agroforestry is thought to have similarities with the potential for carbon sequestration in forests through carbon storage sources on the ground surface. Agroforestry models based on robusta coffee (Coffea canephora) are found in Indonesia, both with simple agroforestry and complex agroforestry types. This research was conducted in Rowosari Village, Sumberjambe District, Jember Regency on several types of robusta coffee-based agroforestry. Based on the results of the study, simple agroforestry has a potential for carbon storage of 73.89% greater than complex agroforestry. The total potential for carbon storage in simple agroforestry is 166.55 tonnes/ha, while in complex agroforestry it is 58.86 tonnes/ha. The potential for carbon storage in agroforestry is affected by the composition of the tree stands. Keywords: agroforestry, biomass, carbon storage